2012
DOI: 10.1029/2011gl050159
|View full text |Cite
|
Sign up to set email alerts
|

Tsunamigenic ionospheric hole

Abstract: Traveling ionospheric disturbances generated by an epicentral ground/sea surface motion, ionospheric disturbances associated with Rayleigh‐waves as well as post‐seismic 4‐minute monoperiodic atmospheric resonances and other‐period atmospheric oscillations have been observed in large earthquakes. In addition, a giant tsunami after the subduction earthquake produces an ionospheric hole which is widely a sudden depletion of ionospheric total electron content (TEC) in the hundred kilometer scale and lasts for a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
129
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 27 publications
12
129
1
1
Order By: Relevance
“…[3] Another prominent phenomenon was significant TEC depletion near the epicenter Saito et al, 2011;Astafyeva et al, 2011;Heki, 2011;Kakinami et al, 2012]. Analyses of the TEC data indicate that TEC decreases suddenly at about 10 min after the onset of the earthquake and reaches the minimum in about 20 min accompanied with some wavy oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Another prominent phenomenon was significant TEC depletion near the epicenter Saito et al, 2011;Astafyeva et al, 2011;Heki, 2011;Kakinami et al, 2012]. Analyses of the TEC data indicate that TEC decreases suddenly at about 10 min after the onset of the earthquake and reaches the minimum in about 20 min accompanied with some wavy oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the TEC data indicate that TEC decreases suddenly at about 10 min after the onset of the earthquake and reaches the minimum in about 20 min accompanied with some wavy oscillations. Kakinami et al [2012] examined the TEC data and concluded that the observed TEC depletion is due to descending motion of ionospheric plasmas at the lower thermosphere followed by the recombination of ions and electrons in the lower ionosphere. They suggested that the downwelling motion in the lower thermosphere is associated with the meter-scale downwelling of sea surface at the tsunami source area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also suggested that similar anomalies were seen in the 27 February 2010 Chile earthquake, and possibly in the 2004 Sumatra-Andaman and the 1994 HokkaidoToho-Oki earthquakes, but not in smaller earthquakes. However, an alternative interpretation of the TEC variation in the ionosphere associated with the 11 March 2011 Tohoku-Oki earthquake is given by Kamogawa and Kakinami (2013) on the basis of the work of Kakinami et al (2012). Their interpretation is that a tsunamigenic ionospheric hole, a wide depletion of the TEC, occurred after the co-seismic acoustic wave reached the ionosphere and gradually recovered at the normal state within several tens of minutes.…”
Section: Introductionmentioning
confidence: 94%
“…지진에서 발견됐던 지진 발생전 TEC의 비정상적인 증가는 사 실이 아니며, 쓰나미 이온 홀(tsunamigenic ionospheric hole, Kakinami et al (2012) (1) Leick, 2004).…”
unclassified